2020
DOI: 10.3389/fgene.2020.00778
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers for CAD Using Integrated Expression and Methylation Data

Abstract: DNA methylation plays an essential role in the pathogenesis of coronary artery disease (CAD) through regulating mRNA expressions. This study aimed to identify hub genes regulated by DNA methylation as biomarkers of CAD. Gene expression and methylation datasets of peripheral blood leukocytes (PBLs) of CAD were downloaded from the Gene Expression Omnibus (GEO) database. Subsequently, multiple computational approaches were performed to analyze the regulatory networks and to recognize hub genes. Finally, top hub g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(54 reference statements)
2
6
0
1
Order By: Relevance
“…Lin et al [46] established an association of PLCB1 gene polymorphisms with the concentration of apolipoprotein B, total cholesterol, and high-density lipoprotein cholesterol in blood. Zhang et al in their recent study [47] identified potential IHD biomarkers (FN1, PTEN, POLR3A), the expression of which is associated with the level of DNA methylation and the risk of IHD. In people with SCD, type 2 diabetes mellitus, and preserved ejection fraction, the expression of the FN1 gene (fibronectin 1) is higher than in those who died from other causes.…”
Section: Dna Methylation and Ischemic Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [46] established an association of PLCB1 gene polymorphisms with the concentration of apolipoprotein B, total cholesterol, and high-density lipoprotein cholesterol in blood. Zhang et al in their recent study [47] identified potential IHD biomarkers (FN1, PTEN, POLR3A), the expression of which is associated with the level of DNA methylation and the risk of IHD. In people with SCD, type 2 diabetes mellitus, and preserved ejection fraction, the expression of the FN1 gene (fibronectin 1) is higher than in those who died from other causes.…”
Section: Dna Methylation and Ischemic Heart Diseasementioning
confidence: 99%
“…Troponin subunit [33] PLA2G7 -phospholipase A2 group VII; 6p12.3 Degradation of platelet activating factor [35] MMP9 -matrix metallopeptidase 9; 20q13.12 Degradation of collagen of IV and V types Hypomethylation of the gene promoter is associated with IHD, higher levels of PTX3 protein in the blood plasma [28] The level of PTX3 protein in the blood plasma is higher in the group with fatal ACS related to coronary thrombosis as compared with the control group [29] as well as in persons with advanced endpoints (including cardiac death) related to the chronic heart failure [30] MMP9 -matrix metallopeptidase 9; 20q13.12 Gene methylation is associated with the risk of IHD, age when it started developing, IHD risk factors [24] The level of MMP-9 in the blood plasma is considered as a risk marker for SCD [39] FN1 -fibronectin 1; 2q35 Gene promoter hypermethylation is associated with IHD [47] Gene expression is higher in people with SCD, type 2 diabetes mellitus, and preserved left ventricular ejection fraction as compared with persons who died from another cause [48] F2RL3 -F2R like thrombin or trypsin receptor 3; 19p13.11 Gene methylation is associated with cardiovascular mortality in case of IHD [50] ABCB1 -ATP binding cassette subfamily B member 1; 7q21.12 Gene promoter methylation is associated with the risk of ischemic events (including cardiac death, myocardial infarction, ischemic stroke) in case of intracranial stenosis [52] FOXP3 -forkhead box P3; Xp11.23 Gene hypermethylation is associated with IHD [17]…”
Section: Gck -Glucokinase; 7p13mentioning
confidence: 99%
“…Pol II transcribes all protein-coding genes and many non-coding RNAs in eukaryotic genomes [ 31 ]. Furthermore, RNA Pol III subunit A is discordantly expressed in CAD individuals [ 32 ]. However, the mechanism of the hnRNPU-actin complex in regulating RNA Pol II transcription is rarely studied in HCAEC growth.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of microarray technology and high-throughput sequencing technology, it provides an opportunity to further understand the genetic and molecular basis of CAD [ 12 , 13 ]. However, most of the current studies focus on the differences between CAD and normal controls, and less attention is paid to the differences between different subtypes of CAD.…”
Section: Introductionmentioning
confidence: 99%